2020
DOI: 10.1039/c9ra08311a
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of co-cultures ofStreptococcus thermophilus and probiotic lactobacilli on quality and antioxidant capacity parameters of lactose-free fermented dairy beverages containingSyzygium cumini(L.) Skeels pulp

Abstract: Probiotic dairy beverages for lactose intolerants had lactobacilli viability above 7 log CFU for 21 days. The co-cultures studied showed proteolytic activity and reinforced the effect of the jambolan pulp on the antioxidant capacity of the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Among the various types of microorganisms that are used as probiotics, selected strains of Lactobacillus acidophilus, Lactobacillus sporogenes, Lactobacillus paracasei, Lactiplantibacillus plantarum, Lacticaseibacillus rhamnosus, Limosilactobacillus reuteri, Limosilactobacillus fermentum, Levilactobacillus brevis, Lacticaseibacillus casei, Lactococcus lactis subsp. cremoris, and Streptococcus salivarius are used for the production of fermented dairy products [19,20]. The health benefits offered by LAB can be nutritional and/or therapeutic, including vitamin production, allergies, and immunoregulation [21]; relief of lactose intolerance symptoms [22]; reduction in the risk of Crohn's disease [23] and diabetes [24]; or even anti-cancer properties [25].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of microorganisms that are used as probiotics, selected strains of Lactobacillus acidophilus, Lactobacillus sporogenes, Lactobacillus paracasei, Lactiplantibacillus plantarum, Lacticaseibacillus rhamnosus, Limosilactobacillus reuteri, Limosilactobacillus fermentum, Levilactobacillus brevis, Lacticaseibacillus casei, Lactococcus lactis subsp. cremoris, and Streptococcus salivarius are used for the production of fermented dairy products [19,20]. The health benefits offered by LAB can be nutritional and/or therapeutic, including vitamin production, allergies, and immunoregulation [21]; relief of lactose intolerance symptoms [22]; reduction in the risk of Crohn's disease [23] and diabetes [24]; or even anti-cancer properties [25].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the growth of Streptococcus thermophilus increased in mixed culture with Lactobacillus acidophilus. Garcia et al [ 54 ] showed the incorporation of Streptococcus thermophilus with lactobacilli strains led to higher acidification and significant reduction in the pH. Besides, Streptococcus thermophilus is always the dominant species in the mixed cultures, with the greatest growth regardless of the substrate [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prebiotics are food ingredients or substances that are not digested in the upper part of the gastrointestinal tract and stimulate the bacterial growth that colonizes the large bowel (Farias, de, de Araújo, Neri‐Numa, & Pastore, 2019; Gibson et al., 2017). Some prebiotics as dietary polyphenols have a close relationship with the intestinal microbiota, influencing the microbiome population (dos Santos et al., 2017; Garcia et al., 2020). It has been estimated that only 5% to 10% of the total polyphenols intake is absorbed in the small intestine; the other 90% to 95% may accumulate in the large intestinal lumen where it is subjected to enzymatic degradation by the gut's microbial population (Yadav, Kumar, Baweja, & Shukla, 2018).…”
Section: Introductionmentioning
confidence: 99%